Photophysical processes related to photoadsorption and photocatalysis on wide band gap solids: A review - Vladimir Ryabchuk (International Journal of Photoenergy)
During the last two decades, various pathways describing photoexcitation of small molecules’ surface reactions at the wide band gap metal oxides and halides (Eg>3 eV) have been recognized. Photogeneration of excitons and free charge carriers may occur in bands of: i) fundamental absorption; ii) extrinsic and intrinsic defect absorption, including those related to surface states; and iii) in UV-induced color centers. Considerable red shifts relative to the fundamental absorption threshold of wide band gap solids have been observed for the spectral limits of surface photoreactions induced in extrinsic absorption bands. This allows thinking about the wide band gap solids as a potential competitors for the relatively narrow band gap photocatalysts. This review discusses the concept of surface photoadsorption (photocatalytic) center while differentiating active and inactive states of the center. Electronically excited defect, surface self-trapped or bound exciton, and the surface defect with trapped photo carrier are considered as the active states of photoadsorption (photocatalytic) centers of different types. The decay pathway of active state determines the lifetime of a photocatalytic center, and in this connection the Langmuir-Hinshelwood kinetic approach is discussed.